An Insight of How the Use of Film/TV and Involvement of Celebrity in Affecting Tourists Travel Decisions to Hong Kong - Ng, Kwok Him Jason (2011)
Hong Kong is one of the world’s most popular tourist destinations; it achieved the ninth world highest tourist receipts in 2010. Hong Kong, also known as “East Hollywood” has nutured many popular actors such as Bruce Lee and Jackie Chan, while its movies and dramas have been successfully attracted international audience. This research paper combines HK film success with the phenomenon “Film Induced Tourism (FIT)” – an inducement effect that attracts viewers to film scenes as tourists. While the world recognises such effect, it actually differs between destinations. The research included the following objectives: